The Impact of Sympathetic Components of Emotional Intelligence on Citizenship Behavior of Physicians - Elham Sahafi; Habibolah Danaee; Mohammad Ali Sarlak; Fedyeh Haghollah (Tehran University of Medical Sciences, 2012)
Objective: One of the most important characteristics of an effective employee performance is person's Sympathetic components of emotional intelligence that has been increasingly considered in an enterprise environment. In this article, we will survey this component in promoting citizenship behavior of physicians. Materials and methods: In a descriptive, co relational and statistical community approach The outstanding performance of an organization using simple random sampling method, 212 cases were included as doctors having subspecialty of the infertility in the Islamic Republic of Iran. A questionnaire was used for data collection. After summarization, structural equation modeling techniques were used for analysis and interpretation of research data. Results: The Sympathetic component has a significant positive impact on organizational citizenship behavior (T=2.90) and this factor with the effect of 0.46% has the impact on organizational citizenship behavior. Conclusion: Considering the importance of sympathy aspect due to results of this research hospital managers are recommended to consider the importance of emotional intelligence in order to enhance the social capabilities of citizenship behaviors of physicians.